2017
DOI: 10.1021/acsinfecdis.7b00024
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Mode of Action of Pantothenamides: Pantothenate Kinase Serves as a Metabolic Activator Not as a Target

Abstract: N-Substituted pantothenamides (PanAms) are pantothenate analogues with up to nanomolar potency against blood-stage Plasmodium falciparum (the most virulent species responsible for malaria). Although these compounds are known to target coenzyme A (CoA) biosynthesis and/or utilization, their exact mode of action (MoA) is still unknown. Importantly, PanAms that retain the natural β-alanine moiety are more potent than other variants, consistent with the involvement of processes that are selective for pantothenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 52 publications
(138 reference statements)
5
42
0
Order By: Relevance
“…It can be difficult to draw SARs with pantothenamides or their analogues, because their antimicrobial activity is affected by multiple factors such as the participation of more than one enzyme during bioactivation, the possible involvement of multiple different targets in the mode of action (as expected for pantothenate antimetabolites), and of course, cell permeability. Our results with triazole derivatives mimicking pantothenamides clearly imply that the 1,4‐substitution pattern on the triazole ring, with a simple methylene linker between the triazole and the pantoyl moieties, can overcome all the mechanistic barriers and display antiplasmodial activity at low nanomolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be difficult to draw SARs with pantothenamides or their analogues, because their antimicrobial activity is affected by multiple factors such as the participation of more than one enzyme during bioactivation, the possible involvement of multiple different targets in the mode of action (as expected for pantothenate antimetabolites), and of course, cell permeability. Our results with triazole derivatives mimicking pantothenamides clearly imply that the 1,4‐substitution pattern on the triazole ring, with a simple methylene linker between the triazole and the pantoyl moieties, can overcome all the mechanistic barriers and display antiplasmodial activity at low nanomolar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It can be difficult to draw SARs with pantothenamides or their analogues, [5,8,10,16,18,24,25,30] because their antimicrobiala ctivity is affected by multiple factors such as the participation of more than one enzyme during bioactivation, the possible involvement of multiple differentt argets in the mode of action (as expected forp antothenatea ntimetabolites), and of course,c ell Table 1. Effect of compounds 6a-b and 8a-i on the proliferation of P. falciparum in the presence of pantetheinases (unlesso therwise noted), reported as the 50 %i nhibitory concentration( IC 50 ), and predicted physicochemical parameters of compounds 1, 2, 6a-b,a nd 8a-i,i ncluding lipophilicity (LogP), molarr efractivity (MR), topological polar surface area (tPSA) or aqueous solubility (LogS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies in bird malaria parasites and recent studies in the human malaria parasite P. falciparum have shown that pantothenate analogs and pantothenamides inhibit intra-erythrocytic development of P. falciparum (Spry et al, 2005, 2010, 2013; de Villiers et al, 2017), and exert their antimalarial activity by possibly inhibiting pantothenate phosphorylation or the phosphorylation of alternative substrates (e.g., pantetheine) and thus blocking CoA biosynthesis. The cellular machinery for the biosynthesis of CoA from exogenous pantothenate involves a putative pantothenate transporter (PAT) and five enzymes, PanK (Pantothenate Kinase), PPCS (Phosphopantothenylcysteine Synthase), PPCDC (Phosphopantothenylcysteine Decarboxylase), PPAT (Phosphopantetheine Adenylyltransferase), and DPCK (Dephospho-CoA Kinase) (Leonardi et al, 2005; Spry et al, 2008).…”
Section: Introductionmentioning
confidence: 99%